Cold Sintered Ceramic Nanocomposites of 2D MXene and Zinc Oxide. Issue 32 (26th June 2018) - Guo, Jing; Legum, Benjamin; Anasori, Babak; Wang, Ke; Lelyukh, Pavel; Gogotsi, Yury; Randall, Clive A.
Abstract: Nanocomposites containing 2D materials have attracted much attention due to their potential for enhancing electrical, magnetic, optical, mechanical, and thermal properties. However, it has been a challenge to integrate 2D materials into ceramic matrices due to interdiffusion and chemical reactions at high temperatures. A recently reported sintering technique, the cold sintering process (CSP), which densifies ceramics with the assistance of transient aqueous solutions, provides a means to circumvent the aforementioned problems. The efficacious co‐sintering of Ti3 C2 Tx (MXene), a 2D transition carbide, with ZnO, an oxide matrix, is reported. Using CSP, the ZnO–Ti3 C2 Tx nanocomposites can be sintered to 92–98% of the theoretical density at 300 °C, while avoiding oxidation or interdiffusion and showing homogeneous distribution of the 2D materials along the ZnO grain boundaries. The electrical conductivity is improved by 1–2 orders of magnitude due to the addition of up to 5 wt% MXene. The hardness and elastic modulus show an increase of 40–50% with 0.5 wt% MXene, and over 150% with 5 wt% of MXene. The successful densification of ZnO–MXene nanocomposite demonstrates that the cold sintering of ceramics with 2D materials is a promising processing route for designing new nanocomposites with a diverse range of applications. Abstract : Ceramic 2D (zinc oxide–MXene) nanocomposites are produced by cold sintering at a temperature as low as 300 °C for 1 h. The electrical and mechanical properties are improved dramatically with the addition of MXene, indicating the potential of the cold sintering process (CSP) in functional nanocomposites.